Adhesion of asphalt mixtures - Mohd. Jakarni, Fauzan (2012)
Adhesion is defined as the molecular force of attraction in the area of contact between unlike bodies of adhesive materials and substrates that acts to hold the bodies together. In the context of asphalt mixtures, adhesion is used to refer to the amount of energy required to break the adhesive bond between bitumen (bitumen-filler mastic) and aggregates. Thus, adhesive failure can be considered as displacement of bitumen (bitumen-filler) mastic from aggregates surface, which might indicates low magnitude of adhesive bond strength. Adhesion is considered as one of the main fundamental properties of asphalt mixtures, which can be correlated with quality, performance and serviceability. However, despite its significance, research on adhesion of asphalt mixtures is limited and yet there is no established testing technique and procedure that can be used to quantify the adhesive bond strength between bitumen (bitumen-filler mastic) and aggregates. Only in the past few years, some efforts have been conducted in developing testing techniques and procedures for measuring the adhesive bond strength of bitumen and aggregates. However, the developed testing techniques and procedures have not enjoyed universal success and acceptance, and not yet established. Hence, emphasis of this study is focused on the development of laboratory adhesion test method that can be used to directly measure the adhesive bond strength between bitumen (bitumen-filler mastic) and aggregates. Also, adhesive bond strength and failure characteristics of various combinations of asphalt mixture materials over wide ranges of testing conditions were evaluated in order to validate the reliability and efficiency of the developed laboratory adhesion test method.